Optimizing use of written peer support as a supportive resource in cancer: Focus group insights. Issue 9 (7th July 2022) - Rini, Christine; Waltz, Margaret; Bovbjerg, Katrin; Farrell, David; Yanez, Betina; Chicaiza, Anthony; Hartstein, Madison L.; Omar, Rahma; Thompson, Rebecca; Rowley, Scott D.; Stanton, Annette L.; Valdimarsdottir, Heiddis; et al.
Abstract: Purpose: Cancer survivors frequently describe wanting to learn from others who have had similar diagnoses or treatments ( peer support ). We conducted focus groups to investigate hematopoietic stem cell transplant survivors' attitudes and preferences regarding accessing written peer support through a website. Although written peer support does not allow for interpersonal interactions with peers, it could increase transplant recipients' access to evidence‐based benefits of informational and emotional peer support. Methods: We conducted four videoconference focus groups with 34 adult transplant survivors who were diverse in their medical and sociodemographic characteristics and geographic location. Discussions were recorded, transcribed, and content analyzed. Results: Many participants reported need for information about transplant beyond what they received from their healthcare providers. Needs varied across participants, as did preferences for characteristics and timing of information optimally provided through peer support. Participants were enthusiastic about the value of written peer support but emphasized that it should be delivered in a way that accommodates variation in transplant experiences, underscores its trustworthiness, and pairs it with useful psychoeducational content. Conclusions: Findings provide guidance for making written peer support an accessible, supportive resource for transplant survivors. Future research should evaluate personalized online delivery of written peer support paired with psychoeducational content that enhances its benefits. Implications for Cancer Survivors: Written peer support delivered online could be a useful, valued resource for transplant survivors.